Operaciones: multiplicación de matrices booleanas, parte 1 - Chavarría-Molina, Jeffry (My University, 2018)
En el presente vídeo se presenta la definición de la multiplicación booleana de matrices, para el caso específico de una matriz final por una matriz columna del mismo número de entradas. El vídeo termina presentando ejemplo numéricos del cálculo de esta operación.

In this video the definition of Boolean matrix multiplication is presented, for the specific case of a final matrix by a column matrix of the same number of entries. The video ends by presenting numerical examples of the calculation of this operation.
Keywords: Operaciones matemáticas; Matrices; Multiplicaciones; Matemáticas discretas; Cálculo númerico; Mathematical operations; Arrays; Multiplications; Discrete mathematics; Numerical operation